2011
DOI: 10.4315/0362-028x.jfp-10-461
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Enterohemorrhagic Escherichia coli Serovar O157 Strains in Clade 8 with Highly Similar Pulsed-Field Gel Electrophoresis Patterns

Abstract: Enterohemorrhagic Escherichia coli serovar O157 (O157) strains with highly similar pulsed-field gel electrophoresis (PFGE) patterns were isolated in Japan during 2007 and 2008. Several genetic features related to O157 evolution were investigated to indicate whether homoplasy might have contributed to the highly similar PFGE patterns in these strains. The O157 strains were classified in lineage I/II, as defined by a lineage-specific polymorphism assay-6 with an atypical allele in Z5935 (code: 231111). Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Epidemiologically unlinked O157 strains were selected for this study so we could analyze genetically diverse strains in subclades 8a and 8b. The genetic diversity of strains derived from a clone is very low [ 21 ], and such strains show very similar levels of Stx2 production. If strains derived from a clone were included in the analysis of subclade 8a and 8b strains, the Stx2 production levels obtained for subclade 8a and 8b strains would be biased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiologically unlinked O157 strains were selected for this study so we could analyze genetically diverse strains in subclades 8a and 8b. The genetic diversity of strains derived from a clone is very low [ 21 ], and such strains show very similar levels of Stx2 production. If strains derived from a clone were included in the analysis of subclade 8a and 8b strains, the Stx2 production levels obtained for subclade 8a and 8b strains would be biased.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study [ 20 ], strains in subclades 8a and 8b isolated in various areas of Japan in the 1990s were analyzed, although that study did not specify the detailed areas or years in which the strains were isolated. Strains of an O157 clone can often emerge and be disseminated in a particular area during a specific time period [ 21 ]. Most strains derived from an O157 clone have very similar genetic features [ 21 , 22 ] e.g., Stx2 production, IS 629 distribution, and possession of pathogenic factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of stx phage insertion sites was done by the method described by Shaikh and Tarr (2003) as previously reported (Yokoyama et al, 2011a). From these results, the O157 strains were divided into subgroups and clusters as described by Leopold et al (2009).…”
Section: Analysis Of Lspa-6 Lineages Stx Phage Insertion Sites and mentioning
confidence: 99%
“…For example, O157 strains with a unique genetic marker were isolated from patients, who were not epidemiologically linked, in various areas of Japan in 2007-2008. Yokoyama et al [41] reported that these strains had very similar pulsed-field gel electrophoresis patterns, indicating that these strains had low diversity.…”
Section: Discussionmentioning
confidence: 99%